Walking a tightrope: the International Criminal Court and conflict prevention in Africa. Issue 1 (2nd January 2017) - Malu, Linus Nnabuike
ABSTRACT: Many African countries gained political independence in the 1960s. This era of independence came with promises and great expectations of economic, political and social development. Fifty years later, it is certain that the promises and expectations of independence have not been easily realised. Perennial violent conflicts have continued to ravage many countries in Africa, causing the catastrophic breakdown of law and order. Therefore, one of the major issues in conflict resolution discourse in Africa is how to develop functional mechanisms for the prevention of violent conflicts. This article examines the capacity of the International Criminal Court (ICC) to act as a mechanism for conflict prevention in Africa. Notwithstanding the doubts and uncertainties associated with the impact of law on conflict transformation, this article argues in the main that the ICC contributes to conflict prevention in Africa by expressing global norms of international law, challenging the culture of impunity in some countries, contributing to general deterrence, speedily intervening in some violent conflicts, and contributing to building some records of atrocities by identifying who did what.